Complete genome sequence of burkholderia gladioli myophage mana - Godoy, Brenda (2021)
Burkholderia gladioli is known to cause respiratory tract infections in cystic fibrosis patients. Here, we describe the annotation of the 38,038-bp genome sequence of Mana, a P2-like phage of B. gladioli. Understanding the genomic characteristics of phages infecting pathogens like B. gladioli can lead to advancements in phage therapy.